Inclusive Shakespeares
XVI, 265 p. 1 illus.
Keywords: Inclusive Shakespeares: Identity, Pedagogy, Performance responds to the growing concern to make Shakespeare Studies inclusive of prospective students, teachers, performers, and audiences who have occupied a historically marginalized position in relation to Shakespeare's poetry and plays. This timely collection includes essays by leading and emerging scholarly voices concerned to open interest and participation in Shakespeare to wider appreciation and use. The essays discuss topics ranging from ethically-informed pedagogy to discussions of public partnerships, from accessible theater for people with disabilities to the use of Shakespeare in technical and community colleges. Inclusive Shakespeares contributes to national conversations about the role of literature in the larger project of inclusion, using Shakespeare Studies as the medium to critically examine interactions between personal identity and academia at large. Sonya Freeman Loftis (co-editor) is Chair of English and Professor of English at Morehouse College, USA, where she specializes in Renaissance literature and disability studies. She is the author of Shakespeare and Disability Studies (2021), Imagining Autism (2015), and Shakespeare's Surrogates (2013), as well as the co-editor of Shakespeare's Hamlet in an Era of Textual Exhaustion (2017). Her work has appeared in Shakespeare Survey, The Disability Studies Reader, Disability Studies Quarterly, and Shakespeare Bulletin. She currently serves on the editorial boards of Journal of Literary and Cultural Disability Studies, Disability Studies Quarterly<, Review of Disability Studies, and Ought: The Journal of Autistic Culture. Mardy Philippian (co-editor) is Associate Professor of English Studies, former Associate Dean for the College of Humanities, Fine Arts, and Communication, and Director of the Literature and Language concentration at Lewis University, USA, where he teaches courses in Shakespeare, Milton, and early modern English literature. Since 2011, he has served as a member of the editorial board of The Oswald Review: International Journal of Undergraduate Research and Criticism in the Discipline of English. His reviews, articles, and book chapters have appeared in Literature and Film Quarterly, Film Criticism, Prose Studies, Forum for World Literature Studies, in the edited collection Recovering Disability in Early Modern England (2013), and in Early Modern Culture. Justin P. Shaw (co-editor) is an Assistant Professor of English at Clark University where his teaching and research explores the intersections of race, emotions, and disability inShakespeare and early modern English texts. He is completing a book project that examines how disability and racial identity are articulated through melancholic discourse in drama, poetry and prose. Committed to both public and traditional scholarship, his work appears in Early Theatre, White People in Shakespeare (Bloomsbury, 2022), and the forthcoming Oxford Handbook of Race, Travel, and Identity in Early Modern England, 1550-1700. He is a former fellow of the James Weldon Johnson Institute for the Study of Race and Difference, has helped to curate exhibits for the Michael C. Carlos Museum such as Desire & Consumption: The New World in the Age of Shakespeare and First Folio: The Book that Gave Us Shakespeare, and has developed the extensive digital humanities project, Shakespeare and the Players.